Karl Polanyi, le marché et le socialisme - Skornicki (2008)
La société est-elle condamnée à subir les lois du marché ? La publication d'Essais inédits de l'économiste Karl Polanyi permet de redécouvrir le (...)
Keywords: capitalisme; fascisme; marché; socialisme

War and Social Change in Modern Europe: The Great Transformation Revisited - Halperin, Sandra (2003)
Halperin traces the persistence of traditional class structures during the development of industrial capitalism in Europe, and the way in which these structures shaped states and state behavior and generated conflict. She documents European conflicts between 1789 and 1914, including small and medium scale conflicts often ignored by researchers and links these conflicts to structures characteristic of industrial capitalist development in Europe before 1945. This book revisits the historical terrain of Karl Polanyi's The Great Transformation (1944), however, it argues that Polanyi's analysis is, in important ways, inaccurate and misleading. Ultimately, the book shows how and why the conflicts both culminated in the world wars and brought about a 'great transformation' in Europe. Its account of this period challenges not only Polanyi's analysis, but a variety of influential perspectives on nationalism, development, conflict, international systems change, and globalization.
Keywords: Great Transformation, The (Book); capitalism; class; critique; nationalism